2021
DOI: 10.1056/nejmoa2109730
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis after BNT162b2 mRNA Vaccine against Covid-19 in Israel

Abstract: Background Approximately 5.1 million Israelis had been fully immunized against coronavirus disease 2019 (Covid-19) after receiving two doses of the BNT162b2 messenger RNA vaccine (Pfizer–BioNTech) by May 31, 2021. After early reports of myocarditis during adverse events monitoring, the Israeli Ministry of Health initiated active surveillance. Methods We retrospectively reviewed data obtained from December 20, 2020, to May 31, 2021, regarding all cases of myocarditis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
582
10
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 518 publications
(686 citation statements)
references
References 6 publications
39
582
10
12
Order By: Relevance
“…We observed no significant increase in EHR reporting of severe adverse events after the 3 rd dose compared with after the 2 nd dose, with incidence comparable with previous literature. 16,17 The observed increase in adverse events compared with earlier doses could be due to a stronger response elicited by the 3 rd dose, comparable to what was observed for the 2 nd dose compared with the 1 st dose. 1,2,33 Further studies are needed to explore whether the 3 rd vaccine dose does indeed induce a stronger immune response.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We observed no significant increase in EHR reporting of severe adverse events after the 3 rd dose compared with after the 2 nd dose, with incidence comparable with previous literature. 16,17 The observed increase in adverse events compared with earlier doses could be due to a stronger response elicited by the 3 rd dose, comparable to what was observed for the 2 nd dose compared with the 1 st dose. 1,2,33 Further studies are needed to explore whether the 3 rd vaccine dose does indeed induce a stronger immune response.…”
Section: Discussionsupporting
confidence: 67%
“…Extensive research has shown that the standard 2-dose regimen of mRNA-based COVID-19 vaccines is relatively safe. Although severe adverse events such as anaphylaxis, 15 myocarditis, 16,17 and blood clotting, [18][19][20][21][22] have been reported after COVID-19 vaccination, these are rare and the benefit of vaccination is deemed to outweigh the potential risks. The most common adverse reactions occur immediately post vaccination 23 and are relatively mild, including headache, fatigue, pains, low-grade fever, and nausea.…”
Section: Introductionmentioning
confidence: 99%
“…However, it represents a significant gap in our knowledge that despite the connection of severe COVID-19 infections and the occurrence of autoantibodies, no systematic clinical study assessing whether COVID-19 vaccination also triggers the production of autoantibodies has been published yet. Such an investigation would be of significant interest especially in view of very recent studies reporting myocarditis after mRNA vaccination especially in younger (< 30 years) male individuals (Barda et al 2021;Mevorach et al 2021;Verma et al 2021;Witberg et al 2021). To address this important question, we here analyzed anti-SARS-CoV2 and autoantibody responses in healthcare workers before and after applying heterologous and homologous vaccination protocols against COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…A study from Israel has reported a higher risk of myocarditis after the second dose, with a rate ratio of 2·35 (95% CI 1·10–5·02) compared with unvaccinated individuals. 9 Is the benefit to risk ratio of the third dose different for older and younger individuals? Concerns exist regarding vaccine-induced thrombotic thrombocytopenia in younger recipients of virus vector vaccines.…”
mentioning
confidence: 99%